Fatal Leishmaniasis in the Absence of TNF Despite a Strong Th1 Response - Fromm, Phillip D.; Kling, Jessica C.; Remke, Annika; Bogdan, Christian; Koerner, Heinrich (Frontiers in Microbiology, 2015)
Induction of inducible nitric oxide synthase in mononuclear phagocytes by IFN-? and innate tumor necrosis factor (TNF) provide the basis for an effective immune response to the intracellular parasite Leishmania (L.) major. In previous experiments, we observed a fatal visceral form of leishmaniasis in L. major-infected C57BL/6 TNF(-/-) mice. To further delineate the protective function of TNF and its receptor requirements, we comparatively assessed L. major-infected C57BL/6 mice that were either deficient for membrane and soluble TNF (Tnf (-) (/) (-)), for soluble TNF alone (memTnf(?/?) ), or the TNF receptors type 1 (Tnfr1 (-) (/) (-)) or type 2 (Tnfr2 (-) (/) (-)). We detected locally and systemically increased levels of the cytokine IFN-? in the absence of the TNF-TNFR1-signaling pathway. An analysis of transcription factors and cytokines revealed that activated Tnf (-) (/) (-) CD4(+) T cells displayed a highly active Th1 phenotype with a strong usage of the T cell receptor V?5.1/2. From these data we conclude that the fatal outcome of L. major infection in Tnf (-) (/) (-) mice does not result from a skewed or deficient Th1 differentiation.
EVALuna2:7701